Mitochondrial Content, but Not Function, Is Altered With a Multimodal Resistance Training Protocol and Adequate Protein Intake in Leucine-Supplemented Pre/Frail Women - Jacob, Kathryn J.; Sonjak, Vita; Spendiff, Sally; Hepple, Russell T.; Chevalier, Stéphanie; Perez, Anna; Morais, José A. (Frontiers in Nutrition, 2021)
Background: Frailty is a clinical condition associated with loss of muscle mass and strength (sarcopenia). Mitochondria are centrally implicated in frailty and sarcopenia. Leucine (Leu) can alter mitochondrial content in myocytes, while resistance training (RT) is the strongest stimulus to counteract sarcopenia and may enhance mitochondrial biogenesis. Objective: We determined the effects of Leu supplementation and RT on mitochondrial content and function in pre/frail elderly women in a randomized double-blinded placebo-controlled study. Methods: Nineteen pre/frail elderly women (77.5 ± 1.3 y, BMI: 25.1 ± 0.9 kg/m2), based on the Frailty Phenotype, underwent 3-months of RT 3x/week with protein-optimized diet and were randomized to 7.5 g/d of Leu supplementation or placebo alanine (Ala). Pre/post-intervention mitochondrial respiration, reactive oxygen species (ROS) production, calcium retention capacity (CRC), time to permeability transition pore (mPTP) opening, mitochondrial voltage-dependent anion channel (VDAC) protein content, leg press 1-repetition maximum (1RM), and 6-minute walk test (6MWT) were measured. Results: No time, supplementation, or interaction effects were observed for respiration, ROS, time to mPTP opening, and CRC. VDAC levels significantly increased in the Leu group post-intervention (p=0.012). Both groups significantly increased leg press 1RM and 6MWT, with no effect of supplementation. Discussion: Leu supplementation with 3 months of RT increased mitochondrial content. Future studies should investigate if there is an increase in mitochondrial turnover or a shift in quality control (mitophagy) in leucine supplemented pre/frail elderly women who undergo 12 weeks of RT. (ClinicalTrials.gov ID: NCT01922167).